2015
DOI: 10.3109/09553002.2015.1027421
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of B-type natriuretic peptide plasma levels in patients with left-sided breast cancer treated with radiation therapy: Results after one-year follow-up

Abstract: BNP plasma levels could provide additional information about subclinical RT-induced cardiotoxicity earlier than traditional ecocardiographic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Increased BNP levels were not associated with manifest or subclinical signs for LV dysfunction or onset of CAD. BNP levels were, however, related to the radiation doses (88,89).…”
Section: Cad and Acsmentioning
confidence: 84%
“…Increased BNP levels were not associated with manifest or subclinical signs for LV dysfunction or onset of CAD. BNP levels were, however, related to the radiation doses (88,89).…”
Section: Cad and Acsmentioning
confidence: 84%
“…While RT potentially leads to accelerated late atherosclerosis, it potentially also leads to early microvascular changes which may manifest as early cardiac perfusion defects. 27,[33][34][35][36][37] Moreover, prior studies found that higher ventricular doses associated with increased troponin levels 38 , increased B-type natriuretic peptide levels 39 , and impaired LV ejection fraction. 40 Although we found weak associations between ACS/CHF events and mean LA and RA dose, these associations might be expected given the multicollinearity between ventricular and atrial doses (Spearman's r ¼ 0.75, p < 0.0001 between mean LV dose and mean LA dose), and were not significant after adjusting for multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…RT-associated ischemic heart disease is thought to result from accelerated late atherosclerosis and early microvascular damage manifesting as perfusion deficits, 3437 and there are also reports linking LV dose to troponin and BNP elevation. 38,39 In a recent analysis of over 900 patients with breast cancer treated with radiation, van den Bogaard et al reported that LV dose had the greatest association with ischemic events. 10 Thus, the common perception that acute coronary syndrome is related to LV dose may also apply to patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%